Seleção de bactérias endofíticas e de ambiente aquático, com potencial para biorremediação, isoladas do Igarapé do Quarenta, na cidade de Manaus-AM. - Manrique, Jorge Luis Rodriguez (2015)
The Manaus city has shown great changes as the economic, social and environmental development, especially with the arrival of Big and important international companies to in Industrial Pole itseft. However, it also brought a significant mass migration of people from all parts of Brazil. The increase of socioeconomic condiction produced in a short period of time generated major environmental problems due to lack of preparation of this city for such a change, seeing themselves affected critically bodies of water, used as a place of discharge of industrial and domestic effluents, and the streams, the Rio Negro and the Amazonas the most affected and, therefore, all the surrounding biodiversity. This is because the surfactant, one of the compounds with the greatest presence in sewage and industrial effluents, can harm both people's health as the fauna, flora and the environment where they are present. However, the microorganisms present in these environments may be able to degrade these compounds. Thus, conduct research with bacteria isolated that surfactants bioremediation ability potential, in this environments, can bring low cost economic alternatives to treatments. The subject of this study was to select cultivable endophytic and aquatic environment polluted bacterias with potential for bioremediation. Samples were taken in two points of the "Igarapé do Quarenta", the first point has high influence of the urban zone and the second has industrial effluents. Water samples were diluted 1/10, grown in LB and NA medium and incubated at 28 °C. The cultures were monitored every 24 hours for 7 days, the growing bacteria were transferred to new petri dishes until an axenic culture was obtained. Vegetal samples were cleaned aseptically, cut, grown in LB and NA medium and incubated at 28 °C. A group of 19 bacteria were selected based in their macro and micro morphology and the isolating points. DNA of the 19 selected bacteria was extracted and amplified (PCR) and biodegradation assays were made. Mineral medium M9 (10 ml) enriched with SDS (150 mg/l) was used to inoculate 100 μl of bacteria. The assays were placed in a shaker at 28°C with 120 rpm for 15 days. Two bacteria decreased the SDS completely. A degradation curve was elaborated with these two degrading bacteria separately and together. The two bacteria achieved the reduction of the SDS faster when worked together (9 days).